PD-1 related transcriptome profile and clinical outcome in diffuse gliomas - Liu, Shuai (Oncoimmunology, 2017)
Background: PD-1 plays a critical part in control of immune response to malignancy. Anti-PD-1 treatment is a hopeful strategy to improve the dismal prognosis of gliomas. To characterize the role of PD-1 in diffuse gliomas, we investigated its related biological process at transcriptome level and its clinical prognostic value. Method and patients: Through Chinese Glioma Genome Atlas and TCGA datasets, we systematically reviewed a total of 994 cases with RNA-seq data and analyzed the functional annotation of PD-1 by Gene ontology (GO) analysis. Univariate and multivariate survival analysis were performed in 907 patients with survival data. Results: We found PD-1 was significantly upregulated in glioblastoma and isocitrate dehydrogenase wild type tumors. According to TCGA transcriptional classification scheme, PD-1 expression was higher in tumors of mesenchymal subtype than other subtypes, and shown good predictive value to mesenchymal subtype. GO analysis revealed that genes significantly correlated with PD-1 were involved in essential functions associated with anti-tumor immune process. Through screening transcriptomic data, we found a strong correlation between PD-1 and immune cell populations especially for T cells. In addition, we investigated the association between PD-1 and genes related to its function, and found that PD-1 was significantly correlated with genes including TGFB1, IDO1, CD40, ICOS and SATB1, and other immune checkpoint molecules including CTLA4, LAG3, TIM3 and CD276. Survival analysis suggested that higher PD-1 expression was independently associated with worse prognosis of patients with diffuse gliomas. Conclusion: Our results indicated that PD-1 was involved in key steps of anti-tumor immune process and independently predicted worse prognosis in diffuse gliomas. These findings may expend our understanding of potential anti-PD-1 treatments.